Analysis of the Impact of Social Media On Teenagers - Dolin Rais; Nurwitria Mamonto; Mery Hariyani; Ansar A Akub; Aditya Machmud (Jurnal Muara Olahraga, 2026)
This study aimed to analyze the impact of social media use among adolescents, focusing on communication, education, self-expression, creativity, and social networking. A descriptive quantitative survey was conducted using a Google Forms questionnaire distributed to 21 adolescent respondents. Data were analyzed using descriptive statistics through frequency and percentage distributions. The results showed that 18 respondents (85.7%) used social media very frequently, while 3 respondents (14.3%) used it frequently. No respondents reported using social media rarely or never, indicating that social media has become an integral part of adolescents' daily lives. The findings suggest that social media positively supports communication, learning, creativity, and self-expression through platforms such as WhatsApp, Instagram, TikTok, and YouTube. However, excessive use may also increase the risk of social media dependency, cyberbullying, and social anxiety. Therefore, promoting digital literacy and responsible social media use is important to maximize its benefits while reducing potential risks.